Innovative Approaches: Integrating Technology into English Language Teaching and Curriculum Design - Napida, Martina; Farhan, Muhammad; Istiara, Febriyantina; Hastomo, Tommy (Universitas Pamulang, 2024)
The motivation behind choosing this topic stems from the increasing importance of technology in education, particularly in teaching English as a foreign language. The researcher aims to explore the various instructional technology tools and resources used by English teachers. The objective of this research is to identify and understand the different types of technology employed in English language teaching and their effectiveness. This qualitative study focuses on two main concepts: the types of instructional technology tools and resources available, and their application in English language teaching. The subjects of the study are two English teachers from SMA Negeri 4 Bandar Lampung. Data was collected through semi-structured interviews, which allowed for in-depth insights into the teachers' experiences and practices. The data collection involved recording and transcribing the interviews, followed by a thematic analysis. This method helped in identifying recurring themes and patterns in the data, which were then systematically organized and analyzed. The findings reveal that English teachers use a variety of technological tools such as projectors, laptops, sound systems, digital textbooks, and online platforms like YouTube and Instagram. These tools not only enhance teaching effectiveness but also increase student engagement and learning outcomes.